The Character of Semar in Wayang: A Synthesis of Javanese Cultural Philosophy and Islamic Principles - Ulfah, Yetty Faridatul; Abbas, Ngatmin; Setiawan, Andi; Ahmad Yasin, Zulfi; Sholehuddin, Yusron (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
The character of Semar in Javanese puppetry is a unique figure who bridges Javanese philosophy and Islamic teachings. This study explores the synthesis between the two traditions through an analysis of Semar's characteristics and teachings. This study aims to (1) analyze how the character of Semar represents the synthesis between Javanese cultural philosophy and Islamic principles, (2) examine its implications for understanding cultural acculturation and (3) its relevance in the context of contemporary Indonesia. This study applied the library research method. Data sources included literature on puppetry, Javanese philosophy, and Islamic teachings. The analysis was conducted by using a hermeneutic, comparative, and semiotic approach. The study result reveal that (1) a significant correlation between the characteristics and teachings of Semar and the basic principles of Islam. Concepts such as "manunggaling kawula gusti" and "memayu hayuning bawana" are in harmony with the teachings of tauhid and khalifah fil ardh in Islam. Simplicity, honesty, and social criticism that characterize Semar are also in line with Islamic values. The synthesis reflected in the character of Semar shows the flexibility of Islam in adapting to local culture without losing the essence of its teachings. (2) This has important implications for understanding Javanese-Islamic cultural acculturation and offers an inclusive and tolerant model of religiosity in the context of contemporary Indonesia. (3) This study also reveals the relevance of this synthesis in facing the challenges of modernity and globalization, as well as its potential in building a national identity that is rooted in local wisdom but open to universal values.